Characterization and Childhood Tumor Risk Assessment of Genetic and Epigenetic Syndromes Associated With Lateralized Overgrowth - Griff, Jessica R.; Duffy, Kelly A.; Kalish, Jennifer M. (Frontiers in Pediatrics, 2020)
Lateralized overgrowth (LO), or segmental overgrowth, is defined as an increase in growth of tissue (bone, muscle, connective tissue, vasculature, etc.) in any region of the body. Some overgrowth syndromes, characterized by both generalized and lateralized overgrowth, have been associated with an increased risk of tumor development. This may be due to the underlying genetic and epigenetic defects that lead to disrupted cell growth and proliferation pathways resulting in the overgrowth and tumor phenotypes. This chapter focuses on the four most common syndromes characterized by LO: Beckwith-Wiedemann spectrum (BWSp), PIK3CA-related overgrowth spectrum (PROS), Proteus syndrome (PS), and PTEN hamartoma tumor syndrome (PHTS). These syndromes demonstrate variable risks for tumor development in patients affected by LO, and we provide a comprehensive literature review of all common tumors reported in patients diagnosed with a lateralized overgrowth related disorder. This review summarizes the current data on tumor risk amongst these disorders and their associated tumor screening guidelines. Furthermore, this chapter highlights the importance of an accurate diagnosis when a patient presents with LO as similar phenotypes are associated with different tumor risks thereby altering preventative screening protocols.